Variation in the ASIP and DUN genes responsible for coat colour in Bosnian mountain horse - Cotman, Marko (Slovenian veterinary research, 2024)
Accurate determination of coat colours in Bosnian Mountain Horse (BMH) can be challenging as there are variations in coat colour shades and several dun dilution vari-ants occur. In other studies found single nucleotide polymorphisms (SNPs) within two colour loci T- box 3 (TBX3) and 11-bp indel polymorphism within Agouti Signalling Proteingene (ASIP), were genotyped in 313 BMH individuals. The obtained genotypes were then compared to the identified phenotypes by using the observed coat colour types from the International Association of Bosnian Mountain Horse Breeders (IABMHB) database. It was found that the dark bay and black were the most representative coat colours in BMH. The frequency of the dominant Dun (D) dilution allele in the study is higher (0.09) than the previously predicted frequency recorded in the available BMH register. Among the identified alleles, there was a discrepancy or inconsistency between the predicted coat colour based on genotypes and the observed coat colour in 73 horses (23%). The most frequent error concerned the misclassification of horses with genotypes aa and Aa at the ASIP gene, non-dun1/non-dun1 (nd1/nd1) and non-dun2/non-dun1 (nd1/nd2) at the TBX3 gene, which can be associated with the occurrence of slight dilution pheno-types in these individuals. In contrast to the Konik and Hucul breeds, no homozygosity of the D allele was found in the BMH. The D allele can be easily overlooked or not rec-ognised in different phenotypic groups, such as dark bay and black horses. Therefore, the hypothesis that Dun dilution effects itself is not as strongly epistatic in the BMH as described in other horse breeds. The results of the study confirm the importance of molecular testing in accurately determining the coat colour of horses. This would help to avoid errors in coat colour descriptions in official breeding records and provide valu-able information for selective breeding programmes aimed at producing specific and desired coat colours.
Keywords: allele frequency; Bosnian mountain horse; DNA polymorphism; dun dilution; genotype frequency; horse coat colour